Application of sensorimotor rhythm on sport performance enhancement - Cheng, M.-Y. (Research & Investigations in Sports Medicine, 2017)
Neurofeedback training (NFT) offers insight into how the mind works. NFT is a technique to maintain electroencephalography (EEG) within an optimal zone that has been related to a desirable behavior by the audio or visual feedback in real time. The basic assumption of EEG NFT is: change the EEG, change the behavior.